Impact of social media on the growth of small business - Евсеева, А. Д.; Соколюк, А. О. (БНТУ, 2019)
The topic of this article is relevant, as nowadays advertising and its placement in various social networks has a great influence on the development of small and medium-sized businesses in general. This technology for placing advertisements in social networks (Instagram, VK, and Facebook) is new and has not yet been fully explored.